Desenvolvimento de metodologia para determinação de diclofenaco em águas superficiais - Romano, Leilaine Elisa (2018)
Emerging contaminants can be defined as chemical compounds in commercial products, which can be recorded in environmental and biological matrices, although they do not have legal regulations yet regarding their disposal and presence in the environment. Drugs as emerging pollutants have stood out among researches due to their impact on the environment and health, for example by impairing surface water quality and so its consumption. The presence of these substances into the environment occurs because of their use to treat diseases in humanbeings and animals. Drugs are, so, realeased by excretion, and also by effluents into water bodies. The consumption of non-steroidal anti-inflammatory drugs by the population has been quite high due to their analgesic and antipyretic properties. Thus, this study aimed at evaluating the presence of diclofenac sodium as an anti-inflammatory drug in river of Cascavel city, Paraná. Water samples were collected from the Cascavel river, from July to November, 2017. Samples were pH adjusted, filtrated and solid phase extracted with SPE cartridges. After elution, the analytes were analyzed by High Performance Liquid Chromatography, using C18 column and UV-VIS detector. The method underwent a validation study, so that linearity, limit of detection and quantification, intermediate precision and recovery were analyzed. The data show that the studied parameters are in accordance with the current legislation on analytical validation. The samples results, analyzed by the proposed method, showed some ranging from 0.70 to 1.06 μg.L-1. Chapter I introduces the scientific paper containing the chromatographic method optimization to determine diclofenac sodium in environmental samples as well as the results concerning its occurrence in the studied samples.